Continuous vs. tapering application of the potent topical corticosteroid mometasone furoate in the treatment of vulvar lichen sclerosus: results of a randomized trial. (1st December 2015) - Borghi, A.; Corazza, M.; Minghetti, S.; Toni, G.; Virgili, A.
Summary: Background: Topical corticosteroids are the first‐line treatment for vulvar lichen sclerosus (VLS). However, evidence on the most appropriate treatment regimen is lacking. Objectives: To compare the effectiveness and tolerability of tapering vs. continuous application of mometasone furoate (MMF) 0·1% ointment in the treatment of active VLS. Methods: Sixty‐four patients with VLS who enrolled in a 12‐week active treatment phase were randomized to apply MMF either (i) once daily for 5 days per week for 4 weeks, then on alternate days for 4 weeks, then twice weekly for 4 weeks (group A) or (ii) for five consecutive days per week for the entire treatment duration (group B). The efficacy parameters were the response rate, the proportion of patients achieving an improvement from baseline of ≥ 75% in subjective and objective scores, and the mean reduction in subjective and objective scores. Results: By the end of the active treatment phase, 27 patients (84%) were considered to be responders in group A, and 25 patients (78%) in group B; 69% and 47% of patients in group A and 62% and 28% in group B achieved ≥ 75% improvement in subjective and objective scores, respectively. The decreases in mean symptom and sign scores were significant compared with baseline with both regimens. No significant differences were found in any of the assessed efficacy end points between the two treatment protocols. Both regimens were well tolerated. Conclusions: Both tapering and continuous application of MMF showed similar efficacy and tolerability in the treatment of active VLS, without any difference in patient adherence to therapy.